2015
DOI: 10.1007/s00167-015-3529-4
|View full text |Cite|
|
Sign up to set email alerts
|

Functional assessments for decision-making regarding return to sports following ACL reconstruction. Part I: development of a new test battery

Abstract: PurposeReturn to activity remains the most common concern following an injury. To facilitate the decision regarding a patient’s return to sport, we developed a standardized and easy-to-use test battery to enable an objective evaluation of knee function.MethodsThe test battery consisted of seven functional tests: the two-leg stability test, one-leg stability test (OL-ST), two-leg countermovement jump (CMJ), one-leg CMJ (OL-CMJ), plyometric jumps, speedy test and quick feet test. For each test, the reliability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
158
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(168 citation statements)
references
References 30 publications
5
158
1
4
Order By: Relevance
“…This term differs from a previous ACLR rehabilitation protocol by van Grinsven et al ,51 who presented a 22-week rehabilitation with four time-based phases. Recent evidence suggests that longer rehabilitation periods are needed, because most patients are not able to reach the end-rehabilitation goals in 22 weeks 129 130. Herbst et al 131 presented a new functional performance test battery and concluded that most patients were not ready for return to play even at 8 months after ACLR.…”
Section: Consensus Conclusionmentioning
confidence: 99%
“…This term differs from a previous ACLR rehabilitation protocol by van Grinsven et al ,51 who presented a 22-week rehabilitation with four time-based phases. Recent evidence suggests that longer rehabilitation periods are needed, because most patients are not able to reach the end-rehabilitation goals in 22 weeks 129 130. Herbst et al 131 presented a new functional performance test battery and concluded that most patients were not ready for return to play even at 8 months after ACLR.…”
Section: Consensus Conclusionmentioning
confidence: 99%
“…Similar to our QMA-RTS programme, their findings demonstrated that the vast majority of patients were not physically ready to return to sport 6 months after surgery according to the goals prescribed. Another test battery included functional tests such as SL and double-leg stability tests and jumps as well as speed tests 23. Their main outcome was the limb symmetry index (LSI).…”
Section: Discussionmentioning
confidence: 99%
“…Dentre os testes de desempenho funcional mais utilizados, destacam-se aqueles que avaliam o desempenho por meio de saltos verticais e em distância, utilizando apoio unipodal e bipodal 5,6 , não apenas em indivíduos saudáveis, mas também em populações específicas como pacientes após reconstrução do ligamento cruzado anterior (LCA), visando o retorno seguro à prática esportiva 5,7 . Entretanto, questiona-se se esses testes são realmente bons preditores de lesão ou recidivas, reforçando a utilização de um conjunto maior de avaliações clínicas para melhor identificar possíveis déficits funcionais 8 .…”
Section: Introductionunclassified